A Linguagem Arquitetônica Tradicionalista: estudo das residências neocoloniais no bairro de Nazaré, em Belém do Pará (1910-1940) - AZEVEDO, Felipe Moreira (Universidade Federal do Pará, 2015)
The study of the Neocolonial architecture that is present in Belém – PA consists of analyze Pará’s architectural history, from that, understanding the intention on its shapes and rethoric which set an important moment for Brazil. Seak for its references as well as for designers of those type of residencial buildings and its periods of constructions, will lead to another way to achieve acknowledge about that architectural phase which, at this city, have gained considerable number of supporters, bequeathing the “quest for freedom” that modern architecture longed to accomplish. This analysis has, by purpose, identify Neocolonial’s stylistic diversity on its production in Nazaré neighborhood at Belém, relating morphological changes occurred in these buildings originally built for residential purposes, through ethnographic and stratigraphical methods practice on each one of three selectioned objects of study, just as well as analyze the compositional grammar and neocolonial buildings morphology in Nazaré neighborhood. Also, it aims to analyze occurred changes, huge impacts, interventions and losses present on the three chosen neocolonial buildings, as well as its relevance to the architectural heritage of Pará and Brazil, from the discussion about its preservation.